Peran Pendidikan Profesi Guru terhadap Kinerja Guru SMA Negeri 1 Belitang, Kabupaten Sekadau - Maria Emakulata; Luhur Wicaksono; Marinu Waruwu (Mathematics Education Study Program, 2025)
This study explores the role of professional teacher education in enhancing teacher performance at SMA Negeri 1 Belitang, Sekadau District. The research emphasizes the importance of professional teacher education in improving pedagogical competence, professional skills, and overall teacher effectiveness. Using a mixed-method approach, this study examines the impact of teacher education programs on teacher performance, focusing on both qualitative and quantitative data. The results indicate that professional teacher education significantly influences teaching quality by increasing teachers' skills, knowledge, and motivation. Furthermore, the study identifies challenges such as inadequate training programs, limited resources, and a lack of support from educational institutions. Recommendations for enhancing teacher education programs include strengthening teacher training, providing ongoing professional development, and improving support systems within schools. The findings highlight the essential role of professional education in shaping the performance and quality of teachers, which ultimately contributes to better educational outcomes.